2015
DOI: 10.1093/intqhc/mzv028
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of facilities and services at Anganwadi centers under the Integrated Child Development Service scheme in Northeast District of Delhi, India

Abstract: This study showed a lack of facilities at the AWCs and poor knowledge of Anganwadi workers. Thus a regular training and supportive supervision of the Anganwadi workers is recommended along with the availability of adequate facilities and infrastructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
1
27
4
Order By: Relevance
“…The purpose of this study was to assess ICDS centre usage among women in ru- [24]. As ICDS centres are one of the most prominent programs for improving childhood health in India [6], future studies of both access to and effectiveness of ICDS programs, especially in the face of major resource shortages, are important. This study should be interpreted within the context of a few limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to assess ICDS centre usage among women in ru- [24]. As ICDS centres are one of the most prominent programs for improving childhood health in India [6], future studies of both access to and effectiveness of ICDS programs, especially in the face of major resource shortages, are important. This study should be interpreted within the context of a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has evaluated ICDS centres by their facilities, the knowledge possessed by their workers, or the effectiveness of specific services [1] [6] [7]. However, few studies have assessed the extent to which ICDS centre services are being utilized [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% anganwadis did not have toilet facility. 5 Poor infrastructure availability can hamper the routine activities in anganwadis. Therefore, the current study was planned to assess the basic infrastructure in anganwadi centres of Punjab.…”
Section: Introductionmentioning
confidence: 99%
“…In study by Malik et al 20% of the AWCs lacked a toilet, while the study by Thakare et al found that 56% of AWCs lacked a toilet facility. 4,8 Half of the AWWs (51.3%) had more than 10 years of working experience. Rathore et al reported that 66.7% AWW had work experience of more than 10 years while 25.9% AWW had experience of 5-10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the ICDS scheme stands with strength of 12.41 lakh AWCs. 4 AWCs delivers services right at the doorsteps of the beneficiaries to ensure their maximum participation. 5 Thus, for the attainment of ICDS scheme goals, each anganwadi center needs to be equipped with adequate infrastructure, functional equipment, tools and drugs.…”
Section: Introductionmentioning
confidence: 99%